The pivotal step of nanoparticle functionalization for the preparation of functional and magnetic hybrid opal films. Issue 11 (26th February 2016) - Scheid, D.; Stock, D.; Winter, T.; Gutmann, T.; Dietz, C.; Gallei, M.
Abstract : An efficient and universal surface modification protocol for silica nanoparticles is reported for the preparation of novel hybrid optical materials. Abstract : The preparation of hierarchical and sophisticated particle architectures for mimicking structural colors known from nature still remains a challenge. In this study, the preparation of novel opal and double-inverse opal films based on thermally treated metallopolymer core particles with a silica shell is described. Thermal treatment leads to the formation of magnetic nanorattle-type particles. The main challenge of artificial particles is to ensure sufficient dispersibility after several synthetic steps. Especially silica particles providing surface hydroxyl groups tend to sinter at high temperatures leading to agglomeration. We present the introduction of trimethyl ethoxy silane (TMES) as an excellent functionalization reagent as the key reaction step. The necessity and success of functionalization are investigated by transmission electron microscopy (TEM) and zeta potential measurements. Importantly, solid state NMR techniques are employed to gain deeper insights into the chemical structure of the surface-attached reagent. Finally, by this convenient functionalization the preparation of elastomeric opal films and double-inverse opal films is proven successful revealing excellent optical film properties. Moreover, magnetic properties of these novel films are investigated by using magnetic force microscopy (MFM). The herein established route is expected to pave the way for the preparation of a variety of advanced and stimuli-responsive optical materials.